(untitled) (Latakia University Journal -Biological Sciences Series, 2021)
The study aimed to identify the most important material and human needs required for establishing a tropical fruit farm in Lattakia Governorate. The data on the studied varieties, such as production quantities, local consumption, costs and prices, were used to assess the characteristics of these varieties. In addition to knowing the climatic characteristics, morphological characteristics and soil components in the studied area, the results showed that the profitability coefficient of the project with respect to costs is 162.87%, meaning that every 100 pounds invested in the project as costs give 162.87 SP, while the profitability factor of the project in relation to the invested capital reached 57 .01%, meaning that every 100 pounds invested in the project gives 57.01 SP. The period of restoring the invested capital has reached 1.75 years, which is considered a good indicator from an economic point of view.